Can Retaliation Moderate The Influence Of Personal Cost, Professional Commitment And Ethical Environment On Pns Interest In Whistleblowing? - Maulidia Dewi Azhari; Sarwenda Biduri; Sigit Hermawan (Universitas Muhammadiyah Malang, 2021)
This study aims to determine whether the retaliation variable can moderate the personal cost, professional commitment, and ethical environment variables in the interest of the Civil Service Inspectorate of Sidoarjo Regency in whistleblowing. This study uses primary data while samples are taken by random sampling by distributing questionnaires through google form to get 45 respondents. This study indicates that the variables of professional commitment and ethical environment have a significant effect on interest in whistleblowing. Still, personal costs are stated to have no effect. The retaliation variable can moderate the influence of the personal cost and ethical environment variables on interest in whistleblowing. So it can be concluded that there is quasi-moderation, which means that the variable that moderates the relationship between the independent variable and the dependent variable and at the same time becomes the independent variable. The results of this study are stated to be very useful for the Sidoarjo Regency Inspectorate; besides that, this research provides input so that the Sidoarjo Regency Inspectorate improves the whistleblowing system flow for internal employees themselves.